Combined intracardiac echocardiography and pressure-sensing catheter for complex PFO closure: a case report - Rui Yan; Xiaofang Li; Jun Li; Xin Shao; Anxin Zhang; Liping Guo; Fanqi Li; Haixiong Wang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundWhile transcatheter closure of a patent foramen ovale (PFO) is usually technically feasible, certain anatomical subtypes such as long-tunnel PFOs can present considerable challenges. Due to the difficulty in advancing the guidewire through the elongated and tortuous tunnel, interventional cardiologists often have to resort to transseptal puncture. However, transseptal puncture is associated with a higher incidence of postoperative residual shunts and an increased risk of puncture-related complications. In this case report, we describe for the first time a novel approach that combines intracardiac echocardiography (ICE) with a pressure-sensing catheter to facilitate guidewire advancement during the PFO procedure. We refer to this innovative technique as the “push and easy” method. This approach offers a promising solution for the closure of complex long-tunnel PFOs while minimizing radiation exposure during the procedure.Case summaryA 20-year-old male patient with a complex long-tunnel PFO was referred to our center. Initial attempts to visualize and traverse the PFO using ICE alone were unsuccessful due to the tunnel's excessive length and tortuosity. Consequently, a pressure-sensing catheter was introduced. This catheter, offering real-time pressure feedback along with enhanced support and maneuverability, enabled successful guidewire passage through the PFO. Under the combined guidance of ICE and the pressure-sensing catheter, precise and safe closure of the complex PFO was achieved, without any radiation exposure. We refer to this novel, radiation-free approach as the “push and easy” technique, which may offer a valuable option for the management of complex long-tunnel PFOs.